Molecular and functional models in neuropsychiatry - Hagan, Jim J. (Current Topics in Behavioral Neurosciences, 2011)
Common neuropsychiatric diseases are associated with significant human and economic cost. The development of more effective treatments requires scientific progress on a broad front and animal models have a vital role to play in these advances, enabling exploration of the functional consequences of molecular changes at the cellular, systems and behavioural levels. This volume discusses some of the latest and most exciting advances in the field. The first five chapters consider developments in gene modification techniques, their applications in vivo across a variety of species and the latest work related to Schizophrenia, Huntington?s Disease and Major Depressive Disorder. Three chapters then focus on recent developments in Autism, Drug Dependence and Attention Deficit Hyperactivity Disorder. In the final four chapters consideration is given to the development of models in larger species and to emergent approaches, such as epigenetic regulation, gene X environment interactions and MRI as a tool for understanding the function of neuronal systems in non- human species, all of which are likely to play an increasingly important role in the scientific discourse related to neuropsychiatric diseases.